From commodity to money: The rise of silver coinage around the Ancient Mediterranean (sixth–first centuries bce). (27th October 2020) - Albarède, F.; Blichert‐Toft, J.; de Callataÿ, F.; Davis, G.; Debernardi, P.; Gentelli, L.; Gitler, H.; Kemmers, F.; Klein, S.; Malod‐Dognin, C.; Milot, J.; Télouk, P.; et al.
Abstract : The reasons why the Western Mediterranean, especially Carthage and Rome, resisted monetization relative to the Eastern Mediterranean are still unclear. We address this question by combining lead (Pb) and silver (Ag) isotope abundances in silver coinage from the Aegean, Magna Graecia, Carthage and Roman Republic. The clear relationships observed between 109 Ag/ 107 Ag and 208 Pb/ 206 Pb reflect the mixing of silver ores or silver objects with Pb metal used for cupellation. The combined analysis of Ag and Pb isotopes reveals important information about the technology of smelting. The Greek world extracted Ag and Pb from associated ores, whereas, on the Iberian Peninsula, Carthaginians and Republican‐era Romans applied Phoenician cupellation techniques and added exotic Pb to Pb‐poor Ag ores. Massive Ag recupellation is observed in Rome during the Second Punic War. After defeating the Carthaginians and the Macedonians in the late second century bce, the Romans brought together the efficient, millennium‐old techniques of silver extraction of the Phoenicians, who considered this metal a simple commodity, with the monetization of the economy introduced by the Greeks.